Eco Excel Solution / Iskandar Zawawi Kamarul Ariffi...[et al.] - Kamarul Ariffin, Iskandar Zawawi; Hisham, Mohamad Aziq Haiqal; Malek, Muhammad Nasrulhaq; Kamarul Hatta, Muhammad Syahrul Naim; Jaafar, Muhammad Hakim (2019)
Our company fairly wish that there are some people is in need for our product. Thus to get to know who in need for our product the customer segment is done. The product is made by our supplier and the we pack them for delivery to our customer. We charge them for our delivery service. We also provide full setup for the product at their house. They can use the product whenever they want. Just throw some waste in the product and let the waste burn. It really helpful especially when there are no any waste management company available at that time.